Communication in Quantum Dot Light Emitting Diode with Optoelectronic Feedback Technique - Attea A.Attea; Hussein B. Al Husseini (University of Thi-Qar Journal of Science, 2020)
A communication scheme based on the synchronization of two chaotic quantum dot light emitting diodes is theoretically examined. The Chaos in the quantum dot light emitting is generated by means of a positive optoelectronic feedback technique. Synchronization of the chaos is achieved by varying coupling strength between the transmitter and the receiver as unidirectional coupling. We then test a proposed chaos shift keying communication scheme by successfully transmitting messages.